- #1

- 685

- 4

## Main Question or Discussion Point

If it's possible to relate the product rule with the binomial theorem, so:

[tex](x+y)^2=1x^2y^0+2x^1y^1+1x^0y^2[/tex]

[tex]D^2(fg)=1f^{(2)}g^{(0)}+2f^{(1)}g^{(1)}+1f^{(0)}g^{(2)}[/tex]

So, is it possible to relate the quotient rule with the binomial theorem too?

[tex](x+y)^2=1x^2y^0+2x^1y^1+1x^0y^2[/tex]

[tex]D^2(fg)=1f^{(2)}g^{(0)}+2f^{(1)}g^{(1)}+1f^{(0)}g^{(2)}[/tex]

So, is it possible to relate the quotient rule with the binomial theorem too?